Pre‐menstrual period: Do women really consume more?. Issue 1 (9th September 2016) - Pastore, Cristina Maria de Aguiar; Francisco‐Maffezzolli, Eliane Cristine; da Silva, Wesley Vieira; Baptista, Paulo de Paula
Abstract: The aim of this study was to investigate female consumption behavior during the different menstrual cycle phases, regarding impulsivity, regret, willingness to pay, and purchase intention for hedonic and utilitarian products. This paper focuses on the gap between literary theory and common sense beliefs. A survey was conducted to 405 women. The results revealed no idiosyncrasy in behavior during the different cycle phases. Impulsive behavior explains the perception of regret; however, hormonal changes throughout the month could not support this correlation, which suggests the reported behavior to be different from the actual one. Copyright © 2016 John Wiley & Sons, Ltd.